Food and status of the Cape clawless otter 'Aonyx Capensis Schinz' in the Tsitsikama Coastal National Park - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2024)
Dissertation (MSc)--University of Pretoria, 1979.